Mediating effect of occupational stress between skeletal muscle disorders and depressive symptoms in firefighters: a Structural Equation Modeling approach - Fengqiong Chen; Liang Wang; Jin Wang; Meiling Liu; Shiwei Cao; Yunxuan Huang; Huaxin Deng; Mengliang Ye (International Journal of Occupational Medicine and Environmental Health)
Objectives The purpose of this study was to explore the relationship between skeletal muscle disorders (SMD), occupational stress (OS) and depressive symptoms (DS) among firefighters.